1986
DOI: 10.1007/bf00586670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine and noradrenaline on Ca channels of cultured sensory and sympathetic neurons of chick

Abstract: The effects of noradrenaline and dopamine on voltage-dependent Ca currents were investigated in cultured dorsal root and sympathetic ganglion neurons from chick embryos. At concentrations of 1 to 10 microM, bath application of the neurotransmitters caused a general depression of inward Ca currents. Above -20 mV the decrease of the current amplitude was reversible and accompanied by a 2-10-fold prolongation of the activation time course. Below -20 mV, where a low voltage-activated Ca component is turned on, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
154
3
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(172 citation statements)
references
References 42 publications
13
154
3
2
Order By: Relevance
“…It closely resembles the one mediated by the G i ␤␥ subunit and associated to most G protein-coupled receptors [41] (see [35] for a review). The main effect of this "membrane-delimited" modulation is a delayed Ca 2+ channel activation at low voltages, which accelerates at higher potentials [42,43]. The slow activation derives from a prolonged latency of first channel opening [44] and is fully recovered by applying strong positive prepulses [45].…”
Section: L-type Versus Non-l-type Channel Modulation By Cannabinoidsmentioning
confidence: 99%
“…It closely resembles the one mediated by the G i ␤␥ subunit and associated to most G protein-coupled receptors [41] (see [35] for a review). The main effect of this "membrane-delimited" modulation is a delayed Ca 2+ channel activation at low voltages, which accelerates at higher potentials [42,43]. The slow activation derives from a prolonged latency of first channel opening [44] and is fully recovered by applying strong positive prepulses [45].…”
Section: L-type Versus Non-l-type Channel Modulation By Cannabinoidsmentioning
confidence: 99%
“…Voltage-dependent inactivation of L-type Ca 2ϩ channels containing cloned ␣ 1C is slower than inactivation of P͞Q-type Ca 2ϩ channels containing cloned ␣ 1A expressed with the same auxiliary subunits in Xenopus oocytes (5,6). In addition, N-type and P͞Q-type Ca 2ϩ channels, but not L-type Ca 2ϩ channels, are modulated by neurotransmitter receptors acting through pertussis toxin-sensitive G proteins via membrane-delimited pathways that cause a positive shift in the voltage dependence of channel activation which is reversed by strong depolarization (9)(10)(11)(12). This modulatory effect is mediated by G protein ␤␥ subunits (13,14), possibly through direct binding to the Ca 2ϩ channel.…”
mentioning
confidence: 99%
“…Several studies suggest that G i/o proteins are involved in the D 2 -mediated modulation of I Ca in various cell types [12,27,30]. In the current studies, PC12 cells were pretreated overnight with 200 ng/ml PTX, which inactivates G i and G o proteins.…”
Section: Ptx-sensitive G Proteins Mediate the D 2 Receptor-induced Inmentioning
confidence: 85%
“…Growing evidence strongly implicates G o rather than G i in this regulation, which could also affect the suppression of neurotransmitter release that is mediated by receptors on presynaptic neurons [4,7,8,28]. Furthermore, membrane-delimited G protein regulation of I Ca by DA has been shown in chick sensory and sympathetic neurons [27]. In addition, a study of rat anterior pituitary cells has shown that the G o α is primarily responsible for the inhibition of Ca 2+ currents induced by D 2 receptor activation [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation